Modelling the impact of tax structure on economic indicators / Taufik Abd Hakim - Abd Hakim, Taufik (2014)
This study attempts to investigate further the recent impact of tax structure on economic indicators in the different group of countries which are the low income, lower middle income, upper middle income and high income countries over the period 2000-2009 (early of modem era). Additionally, the gap between traditional schools of thought which believe that lower income tax rates generate economic growth, while modem schools of thought propagate that higher income tax rates produce economic growth especially for high income countries (Slemrod, 2003; Bonu and Pedro, 2009) motivate researcher to reveal the impact of taxes among group of countries. In this study, researcher specifies models to relate tax structure and economic indicators and estimates them using several advanced econometric approaches which are, 1) the Feasible Generalized Least Squares (FGLS), 2) Two Stage Instrumental Variables (2S-IV), 3) Fixed and Random Effects Instrumental Variables (FE/RE-IV) and, 4) Arellano-Bond Generalized Method of Moments (GMM) estimators. The general finding implies that taxation in lower middle income and upper middle income countries has burdened the economic growth, while for high income countries it has contributed to stimulate economic growth. These results are contrastive with previous studies on tax and support the theory of taxes by modern schools of thought. Evidences from developing countries suggest that total tax revenue (TAX); taxes on income, profits and capital gains (INCOMETX) and highest marginal tax rates (MTR) are highly significant and negatively related to the economic growth. In contrast, the results for high-income OECD countries show that INCOMETX and MTR are significant and positively related to the economic growth. Therefore, this study concludes that, inconsistent impact of taxes is due to the different optimum level of tax rates among the group of countries.